Structural, Thermoanalytical and Antitumour Studies of Metal Chelates of Anthracene-9-Carboxaldehyde Thiosemicarbazone - Thomas, Joby; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
The reactions of thiosemicarbazone of anthracene-9-carboxaldehyde with acetates of manganese(II), cobalt(II) and nickel(II) gave solid complexes which were characterized by various physico-chemical methods such as microanalysis, magnetic measurements, conductivity experiments, electronic and infrared spectral studies. They were found to be of the following formulae [MnL2(H2O)2], [CoL2] and [NiL2] where L = monoanion of the ligand anthracene-9-caboxaldehyde thiosemicarbazone, (A9CTSC). The ligand and the chelates were screened for their possible antitumour activity. The thermal decomposition kinetics and mechanism of these chelates were studied from TG and DTA techniques.